ETHNOMEDICAL STUDY AND IRON CONTENT OF SOME MEDICINAL HERBS USED IN TRADITIONAL MEDICINE IN COTE D’IVOIRE FOR THE TREATMENT OF ANAEMIA - Kone, Witabouna Manidou; Koffi, A G; Bomisso, E L; Tra Bi, F H (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Medicinal plants have been a source of succour in the control of many diseases in developing countries and anaemia is no exception. In this study, ethnomedical survey was carried out for recording medicinal plants used in Northern and South-Eastern Côte d’Ivoire against anaemia. Also iron content was determined for some of the recorded plants using phenanthroline method. Thirty (30) medicinal plants, covering 28 genera and 22 families were recorded. These plants were used to prepare 30 receipts for the treatment of anaemia and aggravating factors such as malaria and gastro-intestinal helminthes. Eleven (11) of these medicinal plants showed presence of iron in various quantities. The most promising were Tectona grandis, Amaranthus spinosus and Stylosanthes erecta which contained the highest iron contents viz; 266.6, 236.6 and 206.6 mg/100 g respectively. They were followed by Hoslundia opposita, Imperata cylindrica, Cajanus cajan, Thalia geniculata and Milicia excelsa. These results lend credence to the traditional use of these plants in Cote d’Ivoire’s ethnomedicine for the treatment of anaemia.